BRINZOLAMIDE-LOADED ETHO-LECIPLEX FOR EFFECTIVE OCULAR MANAGEMENT OF GLAUCOMA: D-OPTIMAL DESIGN OPTIMIZATION AND IN VIVO EVALUATION - EL-HELALY, SARA NAGEEB; HAMMOODI, HAYDER A.; TADROS, MINA I.; ELKASABGY, NERMEEN A. (International Journal of Applied Pharmaceutics, 2024)
Objective: Brinzolamide (BRZ) is an active carbonic anhydrase inhibitor adopted for glaucoma management. The limited aqueous solubility of the drug restricts its potential for ocular administration. Therefore, the aim of this investigation was to design a nanocarrier system called Etho-Leciplex (Etho-LPs) for the delivery of BRZ. Methods: Etho-LPs were fabricated by a simple one-step technique and then optimized by D-optimal design employing Phospholipon®90G (PC): surfactant ratio and surfactant type (Cetyl Trimethyl Ammonium Bomide (CTAB) and Searylamine; SA) as independent variables, whereas the dependent variables were Entrapment Efficiency (EE%), Particle Size (PS), Polydispersity Index (PDI), and Zeta Potential (ZP). Design Expert® statistically suggested the optimum Etho-LP, which consisted of PC: Surface Active Agent (SAA) molar ratio (X1) of 1:1.27 and mixture of CTAB and SA (X2) in 1:1 molar ratio. Results: The optimum Etho-LPs particles had spherical morphology, and EE% of 91.12±0.2 %, PS of 76.21±1.21 nm, PDI of 0.421±0.001 and ZP of 35.88 ±0.10 mV. The in vitro release study results demonstrated that BRZ is rapidly liberated from the optimum Etho-LPs compared to BRZ-suspension. Further, the optimum Etho-LP showed good mucoadhesive properties besides potential safety on rabbits’ eyes tissues. The optimum Etho-LP was found to enhance the ocular bioavailability of the drug in rabbits’ eyes relative to the BRZ suspension. In addition, histopathological assessment indicated the safety of BRZ-loaded Etho-LPs. Conclusion: Overall, the obtained outcomes indicated the effectiveness of employing Etho-LPs for the treatment of glaucoma.